Epidemiological analysis of patients diagnosed with vascular acute abdomen in a complementary care hospital in the city of São Paulo/SP, Brazil: a retrospective study - Garcia, Diego; Souza, Patrícia; Tonhosolo, Renata; Ilias, Elias; Fernandes, Paulo; Silva, Caio; Mincis, Daniela; França, Carolina (Brazilian Journal of Global Health, 2022)
OBJETIVO: Avaliar perfil epidemiológico, clínica e prognóstico de pacientes com abdome agudo vascular (AAV), enquadrados como isquemia mesentérica aguda (IMA) submetidos à cirurgia. MÉTODOS: Foram revisados prontuários de pacientes com IMA, submetidos à cirurgia no Hospital Sancta Maggiore, São Paulo/SP, Brasil; entre janeiro de 2017 a agosto de 2021. Para análise dos dados, utilizou-se o programa SPSS versão 18.0, testes t Student independente e Quiquadrado. RESULTADOS: Foram selecionados 18 pacientes com idade mediana de 78 anos. O principal antecedente pessoal foi hipertensão e 63% relatavam dor abdominal forte à admissão. 47% tiveram o tempo porta-centro-cirúrgico menor que um dia, com tempo cirúrgico menor que 1 hora em 44% dos casos. 31% permaneceram na enfermaria por mais de sete dias e 40% permaneceram na UTI de 1 a 3 dias. 67% dos pacientes vieram a óbito. Não houve diferenças significantes entre pacientes graves e extremamente graves. Em idosos, destaca-se o AAV, condição rara com alta mortalidade, tende a ser mais incidente e pode mimetizar abdomes agudos: obstrutivo, inflamatório e/ou perfurativo. CONCLUSÃO: O AAV é um desafio diagnóstico e terapêutico com provável futura incidência aumentada. Cabe aos cirurgiões obter conhecimento necessário para diagnosticá-lo e tratá-lo visando diminuir sua morbimortalidade. DESCRITORES: Abdome agudo, Isquemia, Isquemia mesentérica, Dor Abdominal. ABSTRACT OBJECTIVE: To evaluate epidemiological, clinical, and prognostic profile of patients with acute vascular abdomen (AVA), framed as acute mesenteric ischemia (AMI) undergoing surgery. METHODS: Medical records of patients with AMI, who underwent surgery at Hospital Sancta Maggiore, São Paulo/SP, Brazil; between January 2017 to August 2021, were reviewed. For data analysis, the SPSS program version 18.0, independent Student t-test and Chi-square tests were used. RESULTS: Eighteen patients with a median age of 78 years were selected. The main personal history was hypertension and 63% reported severe abdominal pain on admission. 47% had door-to-surgery time less than 1 day, with surgical time less than 1 hour in 44% of cases. 31% stayed in the ward for more than 7 days and 40% stayed in the ICU for 1 to 3 days. 67% of the patients died. There were no significant differences between severe and extremely severe patients. In the elderly, AVA stands out as a rare condition with high mortality, tends to be more incident and may mimic acute abdomen: obstructive, inflammatory and/or perforative. CONCLUSION: AVA is a diagnostic and therapeutic challenge with likely future increased incidence. It is up to surgeons to obtain the necessary knowledge to diagnose and treat it to decrease its morbidity and mortality. DESCRIPTORS: Acute Abdomen, Ischemia, Mesenteric Ischemia, Abdominal Pain.